Pendidikan Global Berbasis AI: Risikoetis dan Pentingnya Moderasi Beragama Sebagai Penyeimbang - Sahril Hamdani; Nurita Ismawati; Achmad Muafi Siddiq; Aldi Firnanda; Novia Shafa Dwijayanti (re-JIEM (Research Journal of Islamic Education Management), 2026)
The purpose of this study is to describe AI-based global education and the risks and importance of religious moderation as a balance in the era of globalization. This study uses a library research method with data sources in the form of scientific books, research journals, and internet articles relevant to the research topic. Data analysis techniques are carried out through the stages of data collection, data reduction, and inference drawing. The results show that AI in education has two sides: benefits and risks. AI can improve learning efficiency, assist in the preparation of assignments, and facilitate access to information. However, the use of AI also has the potential to pose risks such as information inaccuracy, decreased critical thinking skills, and threats to privacy and data security. The application of AI needs to be balanced with the values ​​of religious moderation that emphasize tolerance, rationality, contextuality, and respect for differences. AI should be positioned as a tool, while the role of humans remains important in verifying, evaluating, and monitoring the information produced. Thus, the synergy between technological advances and religious ethical principles is key to creating an inclusive and sustainable educational ecosystem. This research provides a conceptual perspective for educators and policymakers to wisely optimize artificial intelligence while strengthening digital literacy and moderate character in students amidst increasingly rapid global dynamics. These implications are expected to serve as a strategic reference in future curriculum development.